Toefl Preparation Class in Non EFL Classroom: How is it Impactful on The Non-EFL Learners’ Achievement? - Angraini, Nike; Iman, Jaya Nur (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2024)
Having problem of reaching the tested aspects of TOEFL particularly on achieving target score of TOEFL set, participants needed to be provided an intervention with TOEFL preparation class before encountering the test. For that reason, this community service activity highlighted the impact of TOEFL preparation class on the non EFL learners’ achievement. One class was used as the sample of this activity in which it consisted of twenty students coming from different major in one of private universities in Palembang, southern region of sumatera. Descriptive analysis with experimental design was used. A test was administered to see whether or not there was a significant improvement on the non EFL learners’ TOEFL-like score achievement. The results revealed that achievement level of the participants were in the elementary and intermediate category. Besides, statistically there was a significant improvement on the EFL learners’ TOEFL-like score intervened by the provision of TOEFL preparation class. Thus, it could be further concluded that TOEFL preparation class was impactful on the non EFL undergaduates’ English achievement. Keywords: TOEFL preparation class; Non EFL Classroom; Non EFL learners’                  achievement